Synthesis and Antibacterial Evaluation of a New Series of N-Alkyl-2-alkynyl/(E)-alkenyl-4-(1H)-quinolones - Abraham Wube; Juan-David Guzman; Antje Hüfner; Christina Hochfellner; Martina Blunder; Rudolf Bauer; Simon Gibbons; Sanjib Bhakta; Franz Bucar (Molecules, 2012)
To gain further insight into the structural requirements of the aliphatic group at position 2 for their antimycobacterial activity, some N-alkyl-4-(1H)-quinolones bearing position 2 alkynyls with various chain length and triple bond positions were prepared and tested for in vitro antibacterial activity against rapidly-growing strains of mycobacteria, the vaccine strain Mycobacterium bovis BCG, and methicillin-resistant Staphylococcus aureus strains, EMRSA-15 and -16. The compounds were also evaluated for inhibition of ATP-dependent MurE ligase of Mycobacterium tuberculosis. The lowest MIC value of 0.5 mg/L (1.2–1.5 µM) was found against M. fortuitum and M. smegmatis. These compounds displayed no or only weak toxicity to the human lung fibroblast cell line MRC-5 at 100 µM concentration. The quinolone derivatives exhibited pronounced activity against the epidemic MRSA strains (EMRSA-15 and -16) with MIC values of 2–128 mg/L (5.3–364.7 µM), and M. bovis BCG with an MIC value of 25 mg/L (66.0–77.4 µM). In addition, the compounds inhibited the MurE ligase of M. tuberculosis with moderate to weak activity showing IC50 values of 200–774 µM. The increased selectivity towards mycobacterial bacilli with reference to MRC-5 cells observed for 2-alkynyl quinolones compared to their corresponding 2-alkenyl analogues serves to highlight the mycobacterial specific effect of the triple bond. Exploration of a terminal bromine atom at the side chain of N-alkyl-2-(E)-alkenyl-4-(1H)-quinolones showed improved antimycobacterial activity whereas a cyclopropyl residue at N-1 was suggested to be detrimental to antibacterial activity.